Preliminary Experience With Transcranial Doppler Monitoring in Patients Undergoing Carotid Artery Revascularization: Initial Observations on Cerebral Embolization Patterns. Issue 3 (September 2021) - Tok Cekmecelioglu, Busra; Legeza, Peter; Sinha, Kavya; Tekula, Pooja; Lumsden, Alan; Garami, Zsolt
Intraoperative transcranial Doppler (TCD) monitoring allows us to see intracranial blood flow changes related to endovascular and surgical manipulation in real time. This study evaluates the results of TCD monitoring during transcarotid artery revascularization (TCAR) with flow reversal, carotid endarterectomy (CEA) without shunt, with a shunt (shCEA), and transfemoral carotid artery stenting (tfCAS) with distal filter protection. Patients who underwent carotid artery revascularization with TCD monitoring were included. Patient demographics and medical history were recorded based on medical documentation. Intraoperative TCD, hemodynamics, fluoroscopy images, and surgical manipulation were recorded simultaneously with a 4-channel video recording system, and based on the recordings, the number of high-intensity signals (HITS) and middle cerebral artery (MCA) flow changes were registered. HITS during contrast injections were not included in the analysis due to the high number of artifacts. HITS were compared between the four groups, and HITS during lesion crossing/predilation/stent deployment/postdilation were compared between the tfCAS and TCAR groups. Thirty six patients were involved (mean age 69.5 ± 10.59 years; 24 male) (9 CEA; 11 shCEA; 4 tfCAS; 12 TCAR). Hypertension, diabetes mellitus, coronary artery disease, and smoking were frequent in all groups. Median number of HITS for CEA, shCEA, tfCAS, and TCAR were 5 (range: 0-90), 10 (range: 3-72), 197.5 (range: 153-340), and 29 (range: 2-74), respectively. The number of HITS during TCAR was not significantly different compared to CEA or shCEA but significantly lower than in patients receiving tfCAS ( P < .01). Procedural phases of lesion crossing, predilation, stent deployment, and postdilation were associated with significantly higher HITS during tfCAS than TCAR ( P = .002, P = .006, P = .04, P = .006, respectively). The number of embolic events during TCAR is comparable with CEA with and without a shunt and associated with a significantly lower HITS rate than tfCAS with distal filter protection. According to our results, TCAR appears to be a safer alternative to tfCAS.